ANALISIS KANDUNGAN UNSUR NPK DALAM KOMPOS ORGANIK LIMBAH JAMUR DENGAN AKTIVATOR AMPAS TAHU - Ahmad Zukni; Hunaepi Hunaepi; Taufik Samsuri (Bioscientist : Jurnal Ilmiah Biologi, 2013)
NPK nutrient elements are essential nutrients that are needed by plants to meet the needs of plant growth. The purpose of this study was to find out how the content of NPK elements in organic compost of mushroom waste with dregs activator know. The type of this research is experimental research that is kind of systematic, logical, and meticulous research in controlling the condition. The results of this study indicate that the compost control with compost treatment of the average yield of NPK has exceeded the minimum standard of SNI of compost fertilizer, with the average number of control elements N = 4.67%, P = 2.92%, and K = 5.13%. In the 10:50 N treatment it reached an average of 3.03%, P reached an average of 2.83%, and K reached an average of 3.29%. At 30:50 N treatment reached 3.50%, P reached an average of 2.98%, and K reached an average of 3.67%. While the 50:50 N treatment reached an average of 1.87%, P reached an average of 2.18%, and K reached an average of 3.19%. Of the three treatments on organic compost of mushroom waste with the activator of tofu waste can be seen that the highest average amount of NPK element is at treatment of 30:50, and the lowest is at 50:50 treatment. It can be concluded that there is no significant difference of NPK element content in organic compost of mushroom waste with dregs activator know in each treatment.